Perlindungan Hukum Terhadap Konsumen Dalam Transaksi E-Commerce - Ahmad Ahmad; Johamran Pransisto; Muh. Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2023)
This study aims to determine the practice of buying and selling, and to find out that regulations on consumer protection are still in accordance with the pattern of buying and selling online. This research uses normative legal research with a literature study approach, types and sources of legal materials using primary legal materials and secondary legal materials. Data analysis will be examined from a qualitative perspective. The results of the research show that online buying and selling practices and regulations on consumer protection have been accommodated in Law no. 8 of 1999 (consumer protection), law no. 31 of 2004 (Engagement), law no. 7 of 2014 (trade) and Law no. 19 of 2016 (ITE).